An Observational Study of Children's Involvement in Informed Consent for Exome Sequencing Research. (February 2017) - Miller, Victoria A.; Werner-Lin, Allison; Walser, Sarah A.; Biswas, Sawona; Bernhardt, Barbara A.
The goal of this study was to examine children's involvement in consent sessions for exome sequencing research and associations of involvement with provider and parent communication. Participants included 44 children (8-17 years) from five cohorts who were offered participation in an exome sequencing study. The consent sessions were audiotaped, transcribed, and coded. Providers attempted to facilitate the child's involvement in the majority (73%) of sessions, and most (75%) children also verbally participated. Provider facilitation was strongly associated with likelihood of child participation. These findings underscore that strategies such as asking for children's opinions and soliciting their questions show respect for children and may increase the likelihood that they are engaged and involved in decisions about research participation.